Drive soil nitrogen transformation and improve crop nitrogen absorption and utilization - a review of green manure applications - Lyu, Hanqiang; Li, Yue; Wang, Yulong; Wang, Pengfei; Shang, Yongpan; Yang, Xuehui; Wang, Feng; Yu, Aizhong (Frontiers in Plant Science, 2024)
Green manure application presents a valuable strategy for enhancing soil fertility and promoting ecological sustainability. By leveraging green manures for effective nitrogen management in agricultural fields can significantly reduce the dependency of primary crops on chemical nitrogen fertilizers, thereby fostering resource efficiency. This review examines the current advancements in the green manure industry, focusing on the modulation of nitrogen transformation in soil and how crops absorb and utilize nitrogen after green manure application. Initially, the influence of green manure on soil nitrogen transformation is delineated, covering processes such as soil nitrogen immobilization, and mineralization, and losses including NH3, N2O, and NO3 − -N leaching. The review then delves into the effects of green manure on the composition and function of soil microbial communities, highlighting their role in nitrogen transformation. It emphasizes the available nitrogen content in the soil, this article discussing nitrogen uptake and utilization by plants, including aspects such as nitrogen translocation, distribution, the root system, and the rhizosphere environment of primary crops. This provides insights into the mechanisms that enhance nitrogen uptake and utilization when green manures are reintroduced into fields. Finally, the review anticipates future research directions in modulating soil nitrogen dynamics and crop nitrogen uptake through green manure application, aiming to advance research and the development of the green manure sector.